2020
DOI: 10.1103/physrevb.101.165114
|View full text |Cite
|
Sign up to set email alerts
|

Level statistics of extended states in random non-Hermitian Hamiltonians

Abstract: Absence of level repulsion between extended states in random non-Hermitian systems is demonstrated. As a result, the general Wigner-Dyson distributions of level spacing of diffusive metals in the usual Hermitian systems is replaced by the Poisson distribution for quasiparticle level spacing of non-Hermitian disordered metals in the thermodynamic limit of infinite system size. This is a very surprising result because Poisson statistics is universally true for the Anderson insulators where energy eigenstates do … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…where s i+1 = Re (E i+1 ) − Re (E i ) denotes the level spacing between the real part of the (i + 1)th and ith eigenenergies [49,56,57]. The average of r i which goes over all the eigenenergies gives rise to r = n r n /L.…”
Section: Non-hermitian Induced Reentrant Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…where s i+1 = Re (E i+1 ) − Re (E i ) denotes the level spacing between the real part of the (i + 1)th and ith eigenenergies [49,56,57]. The average of r i which goes over all the eigenenergies gives rise to r = n r n /L.…”
Section: Non-hermitian Induced Reentrant Localizationmentioning
confidence: 99%
“…These exotic phenomena bring potential applications including lasing [31][32][33], sensing [34][35][36][37][38], and topological light modulation [39][40][41]. Particularly, the interplay between disorder and non-Hermiticity has been recently explored [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In non-Hermitian quasiperiodic lattice with asymmetric hopping or PT -symmetry, it is revealed that the non-Hermitian Anderson transition coincides with topological transition and complex-real energy transition [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the study on disorder effect in non-Hermitian systems has also drawn extensive attentions [80][81][82][83][84][85][86][87][88][89][90][91][92][93]. Importantly, the NHSE could still exist in disordered samples [12][13][14][15][16][17] and leads to the breakdown of BBC for translational-symmetry-broken samples.…”
mentioning
confidence: 99%
“…Although has achieved great successes in clean systems, the applicability of GBZ theory in disordered systems is still not fully understood because this theory is heavily based on the translational symmetry [52][53][54]. Therefore, the widely adopted GBZ theory may not be directly applicable [96] when disorder is presented [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. The BBC mechanism as well as the quantitative description of the NHSE in disordered samples remain to be investigated.…”
mentioning
confidence: 99%
“…Many theoretical and experimental works show that non-Hermicity gives rise to different phenomena that do not occur in a Hermitian system [50][51][52][53][54][55][56][57][58][59][60][61]. For instance, Poison distribution, universal level-spacing statistics of localized states in Hermitian systems, becomes quasi-particle level spacing statistics in metallic phases of non-Hermitian systems [62,63]. Moreover, a modified bulk-boundary correspondence is established to describe the non-Hermitian topological states of Su-Schrieffer-Heeger models [52,54,55], CIs [53,[64][65][66], and quantum spin Hall insulators [67].…”
mentioning
confidence: 99%